Barcoding Atlantic Canada’s mesopelagic and upper bathypelagic marine fishes - Kenchington, Ellen L. (PLoS One, 2017)
DNA barcode sequences were developed from 557 mesopelagic and upper bathypelagic teleost specimens collected in waters off Atlantic Canada. Confident morphological identifications were available for 366 specimens, of 118 species and 93 genera, which yielded 328 haplotypes. Five of the species were novel to the Barcode of Life Database (BOLD). Most of the 118 species conformed to expectations of monophyly and the presence of a “barcode gap”, though some known weaknesses in existing taxonomy were confirmed and a deficiency in published keys was revealed. Of the specimens for which no firm morphological identification was available, 156 were successfully identified to species, and a further 11 to genus, using their barcode sequences and a combination of distance- and character-based methods. The remaining 24 specimens were from species for which no reference barcode is yet available or else ones confused by apparent misidentification of publicly available sequences in BOLD. Addition of the new sequences to those previously in BOLD contributed support to recent taxonomic revisions of Chiasmodon and Poromitra, while it also revealed 18 cases of potential cryptic speciation. Most of the latter appear to result from genetic divergence among populations in different ocean basins, while the general lack of strong horizontal environmental gradients within the deep sea has allowed morphology to be conserved. Other examples of divergence appear to distinguish individuals living under the sub-tropical gyre of the North Atlantic from those under that ocean’s sub-polar gyre. In contrast, the available sequences for two myctophid species, Benthosema glaciale and Notoscopelus elongatus, showed genetic structuring on finer geographic scales. The observed structure was not consistent with recent suggestions that “resident” populations of myctophids can maintain allopatry despite the mixing of ocean waters. Rather, it indicates that the very rapid speciation characteristic of the Myctophidae is both on-going and detectable using barcodes.